GENETIC DIVERSITY, HERITABILITY AND CORRELATION BETWEEN LOCAL CULTIVARS OF UPLAND RICE - mustakim mustakim; sakka samudin; maemunah maemunah (Tadulako University, 2019)
Paddy is one of the important cereal crops as food a main food for a third of the world's population, including Asia. Production of paddy rice plants can be improved through plant genetic improvement. The ebjective of this study was examine the genetic diversity, heritability, and correlation between the characteristics of several local upland rice cultivars. This study was carried out in Tamarenja Village, Sindue District, Donggala Regency, Central Sulawesi Province. It was began in May to October 2018. A Randomized Block Design with eight cultivars as a genotypic treatment and reapeted three times was used in this study. There were 24 trial plots in total. Variables observed included plant height, number of leaves, length of leaves, number of tillers, number of productive tillers, age of panicle exit, panicle length, harvest age, number of seeds per panicle, seed length, seed diameter, weight of 100 seeds, and total yield. The results showed that the genetic influences were more dominant than the environment on all observed variables except the weight of 100 seeds and seed diameter. The number of seeds per panicle, the number of tillers and the number of productive tillers were traits that have a high value on heritability and genetic progress. Panicle length, seed diameter and weight of 100 seeds were characteristics that have a high genetic correlation coefficient on upland rice yields. The weight of 100 seeds has a direct influence and high genetic correlation to the results so that it can be used as a direct selection criterion to increase upland rice yields.